2014
DOI: 10.3389/fnhum.2014.00482
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of phonological ability, speech perception, and auditory perception in adults with dyslexia

Abstract: This study investigated whether auditory, speech perception, and phonological skills are tightly interrelated or independently contributing to reading. We assessed each of these three skills in 36 adults with a past diagnosis of dyslexia and 54 matched normal reading adults. Phonological skills were tested by the typical threefold tasks, i.e., rapid automatic naming, verbal short-term memory and phonological awareness. Dynamic auditory processing skills were assessed by means of a frequency modulation (FM) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 69 publications
5
56
0
3
Order By: Relevance
“…Assessment methods followed the same procedures as those expressed in Law et al . () and are described as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Assessment methods followed the same procedures as those expressed in Law et al . () and are described as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Although many studies focused on deficiencies in perceiving consonants, the perception and production of vowels is also less precisely defined (Bertucci, Hook, Haynes, Macaruso, & Bickley, 2003;Stark & Heinz, 1996). Although a large number of studies showed perception deficits in DD, it should be noted that speech perception deficits were not always found in the majority of people with DD (Manis et al, 1997), not for all phonetic contrasts (Cornelissen, Hansen, Bradley, & Stein, 1996), and not always in silent (Ziegler et al, 2009) or in noise conditions (Hazan, MessaoudGalusi, & Rosen, 2012;Law, Vandermosten, Ghesquiere, & Wouters, 2014). Although the majority of studies show that people with DD have deficient perceptual abilities, resulting in less precise or degraded phonological representations, another perspective on the perception deficit comes from Serniclaes, Van Heghe, Mousty, Carré, and SprengerCharolles (2004).…”
Section: A Phonological Processing Deficit In Ddmentioning
confidence: 99%
“…The theory is that if readers perceive basic acoustic cues poorly, the result will be inaccurate perception of speech sounds that necessarily map poorly onto the visual symbols (letters) for reading (Law et al 2014; McAnally and Stein 1996). Studies on the development of reading and reading disability or dyslexia , also support a theory known as the auditory deficit hypotheses of reading (Boets et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, including those that included children at risk for dyslexia due to family history, report significant associations between either AM or FM modulations and specific skills associated with reading development (Boets et al 2007). Specifically, AM perception tasks, though varying in exact parameters and sometimes referred to as “rise time” in the literature, have been associated with phonological awareness, syllable detection and non-word reading (Goswami et al 2002; Hamalainen et al 2013; Law et al 2014). Likewise, increased FM thresholds have predicted reduced non-word and single word reading performance (Talcott et al 2003; Talcott et al 2000; Witton et al 2002).…”
Section: Introductionmentioning
confidence: 99%